Studi Kasus Penderita Skizofrenia Paranoid - . Ningnurani; Muslimah Zahro Romas; Fx. Wahyu Widiantoro (Jurnal Psikologi, 2022)
Paranoid schizophrenia is the type of schizophrenia that is most often found in any country. The clinical picture is dominated by relatively stable views, often paranoid, usually accompanied by hallucinations especially auditory hallucinations and perception disorders (positive symptoms). Hearing hallucinations are the most common character of psychotic symptoms. This study aims to determine the description of the sufferers of paranoid schizophrenia. This study uses a case approach method that is included in the qualitative research model. Two subjects participated in this research. Data collected through observation, interviews and documentation. Based on the results of interviews and observations it is known that participants have all the special characteristics of paranoid schizophrenia. Overall the subject is a closed person, anxious, unable to get along with the environment and withdraw. The subjects also felt they could not have an important role in the family. Subjects are people who are full of anxiety, aggressive, easily emotional, impulsive, paranoid, and schizophrenic tendencies.